Human L-ferritin deficiency is characterized by idiopathic generalized seizures and atypical restless leg syndrome - Cozzi, Anna; Santambrogio, Paolo; Privitera, Daniela; Broccoli, Vania; Rotundo, Luisa Ida; Garavaglia, Barbara; Benz, Rudolf; Altamura, Sandro; Goede, Jeroen S.; Muckenthaler, Martina; Levi, Sonia (Journal of experimental medicine, 2013)
The ubiquitously expressed iron storage protein ferritin plays a central role in maintaining cellular iron homeostasis. Cytosolic ferritins are composed of heavy (H) and light (L) subunits that co-assemble into a hollow spherical shell with an internal cavity where iron is stored. The ferroxidase activity of the ferritin H chain is critical to store iron in its Fe3+ oxidation state, while the L chain shows iron nucleation properties. We describe a unique case of a 23-yr-old female patient affected by a homozygous loss of function mutation in the L-ferritin gene, idiopathic generalized seizures, and atypical restless leg syndrome (RLS). We show that L chain ferritin is undetectable in primary fibroblasts from the patient, and thus ferritin consists only of H chains. Increased iron incorporation into the FtH homopolymer leads to reduced cellular iron availability, diminished levels of cytosolic catalase, SOD1 protein levels, enhanced ROS production and higher levels of oxidized proteins. Importantly, key phenotypic features observed in fibroblasts are also mirrored in reprogrammed neurons from the patient’s fibroblasts. Our results demonstrate for the first time the pathophysiological consequences of L-ferritin deficiency in a human and help to define the concept for a new disease entity hallmarked by idiopathic generalized seizure and atypical RLS.